2019
DOI: 10.5194/acp-19-15183-2019
|View full text |Cite
|
Sign up to set email alerts
|

The unprecedented 2017–2018 stratospheric smoke event: decay phase and aerosol properties observed with the EARLINET

Abstract: Six months of stratospheric aerosol observations with the European Aerosol Research Lidar Network (EAR-LINET)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 65 publications
2
76
0
2
Order By: Relevance
“…Instead, we propose a much simpler model of compact near-spherical particles. Our starting point and main assumption is that the particle near-spherical shape can be highly depolarizing, as shown in the work of Mishchenko and Hovenier (1995) and Bi et al (2018). Our analysis shows that for the Canadian stratospheric smoke observed above Europe in August 2017, the PLDR and LR measurements along with their spectral dependence can be successfully reproduced with the proposed model of compact near-spherical particles.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Instead, we propose a much simpler model of compact near-spherical particles. Our starting point and main assumption is that the particle near-spherical shape can be highly depolarizing, as shown in the work of Mishchenko and Hovenier (1995) and Bi et al (2018). Our analysis shows that for the Canadian stratospheric smoke observed above Europe in August 2017, the PLDR and LR measurements along with their spectral dependence can be successfully reproduced with the proposed model of compact near-spherical particles.…”
mentioning
confidence: 60%
“…As the particles age in the atmosphere, this aggregate structure collapse; the particles become more hydrophilic and are frequently found covered by cells composed of water-soluble components such as sulfates or organic materials (Worringen et al, 2008;Wu et al, 2016). Due to the aforementioned processes, the PLDR of smoke particles may present a large variability related to the age of the particles (Baars et al, 2019), the presence of other aerosol types found inside the smoke layers (Tesche et al, 2009;Groß et al, 2011Groß et al, , 2013 or even the particle water uptake due to different humidity conditions (Cheng et al, 2014). These processes alter smoke particle shape, size and composition, resulting in PLDR values that may vary from 2 % to 10 % at 532 nm for aged and fresh smoke.…”
mentioning
confidence: 99%
“…When long-range transported, biomass burning aerosols abate their absorbing efficiency (Nicolae et al, 2013) complicating climatic impact calculations. Biomass burning aerosols are spherical to nearly-spherical in shape (Gialitaki et al, 2020) and their shape is transforming to more spherical while aging and coating of the BC particles (Baars et al, 2019).…”
Section: Other Aerosol Typesmentioning
confidence: 99%
“…Respecto a la distribución vertical, las partículas de aerosol se encuentran principalmente en los primeros kilómetros de la atmósfera cerca de sus respectivas fuentes, es decir, dentro de la baja troposfera y excepcionalmente en la alta troposfera y baja estratosfera debido a fuertes erupciones volcánicas o grandes incendios forestales [e.g. Sawamura et al, 2012;Baars et al, 2019]. La distribución de las partículas nubosas es aún más compleja y no es nada uniforme ni en el tiempo ni en el espacio.…”
Section: Iii1 La Atmósfera Y La Interacción Radiación-materiaunclassified
“…Como su atmósfera no está contaminada con partículas de origen antropogénico, presenta condiciones idóneas para el estudio de capas transportadas de humo y polvo mineral [Preißler et al, 2011[Preißler et al, , 2013Pereira et al, 2009Pereira et al, , 2014Valenzuela et al, 2017]. En concreto, las capas de humo pueden tener diferentes procedencias, desde incendios producidos dentro de las fronteras nacionales [Pereira et al, 2014] o grandes incendios forestales en Norte América [Baars et al, 2019;Sicard et al, 2019]. De manera extraordinaria también se han detectado capas con composiciones significativas de partículas de aerosol volcánico, durante el periodo de gran actividad del volcán Eyjafjallajökull, Islandia, en 2010 [Sicard et al, 2012].…”
Section: Iv2 Estación De Superficie En éVoraunclassified